Homo- and Heterotypic Trajectories in a Preschool to Primary-School Clinical Sample: A Prospective Study Related to Maternal Psychopathology - Jobs, Isabell; Müller, Jörg Michael; Skorozhenina, Olena; Romer, Georg (Frontiers in Psychiatry, 2019)
Background Most longitudinal or follow-up mental health studies describe developmental pathways using dimensional measures of psychopathology, but seldom using pathways described by clinical disorders. Objective We aim to describe diagnostic pathways by homotypic (within the disorder continuity) and heterotypic development (between the disorder continuity), with maternal psychopathology as moderator for both trajectories. Methods Clinically referred children (0-7 years; N = 83) were assessed at preschool age and at primary-school age through a clinical interview. We built a disorder cluster of emotional disorders (ED; F32, F40, F42, F43, F93.0, F93.1, F93.2, F93.8, F95), behavioral disorders (BD; F68.8, F90, F91, F91.3, F93.3, F93.9, F94), and specific early onset disorders (SEO; F50, F51, F70, F98.0, F98.1, F98.2, F98.8, F98.9). We describe the prevalence, comorbidity, and clinical trajectories of various types of homotypic and heterotypic development. Results We observed a high rate of comorbidity throughout the study (62.6% at admission and 67.5% at follow-up) and in general, a high continuity of mental health problems from preschool to primary-school age children (69.9% of the sample showed continuity), with 50.6% of the sample showing homotypic and 44.6% showing heterotypic development. Hierarchical multiple regression analyses suggest that heterotypic development may be influenced by maternal psychopathology. Conclusion Currently, evidence-based mental health guidelines for preschool populations are designed and evaluated assuming a homotypic development. However, our findings indicate that treatment interventions and outcome measures should also be designed and evaluated for heterotypic development especially in case of increased maternal psychopathology.